Evaluation of Attrition Rate among University Freshmen in South West, Nigeria (2010)
Entering the university creates a lot of excitement for university freshmen. This is particularly so when the competitive nature of admission into the university is considered. The joy and the boasting associated with gaining admission into tertiary institution are not limited to the students alone as their parents and relatives are part of the celebration. This,study is designed to determine the attrition rate among the university freshmen and to determine the attrition rate among male and female universities freshmen in the south west, Nigeria. Ex-post facto design was employed in this study. 2518 university freshmen in the federal universities in south west Nigeria were used, with 1423 males and 1095 females. Secondary data were collected from the concerned universities' records office. Descriptive statistics and t-test analysis were used to analyze the two research questions that were raised at 0.05 levels of significance. However, there was no significant difference in the attrition rate of male and female university freshmen and the attrition rate is 7.1%. Based on the findings of this study, it was recommended that parents should see to the education need of their children early enough. That school counsellors and education stakeholders should try as much as possible to boost academic self-efficacy of learners.